(3SdhI GdhLjR aj TQM CMGOjK SdSdI GdGHQjRs - (3UGdM Hf UOjb Hf Ydj, CHh GdecGQe fhQ GdOjf GdCfUGQj GdNRQLj GdfeGRj,J (B975 (3g` s
(3ChdgG (B:s
(3hHYO agPG TQM dWja hQeR eJbf hSejJg Gdbhd GdhLjR s
(3BNQgG (B:s
(3hgj bUjOI eHGQcI dgG cQGeGJ hHQGgjf cKjQI faY Gddg HgG hHHQcJgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B192 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B7s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs